Dynamic expression of proteins associated with adventitial remodeling in adventitial fibroblasts from spontaneously hypertensive rats - Guo, Shu-jie (Nature Publishing Group, 2010)
AIM: To identify proteins that could potentially be involved in adventitial remodeling in vascular adventitial fibroblasts (AFs) from spontaneously hypertensive rats (SHR). METHODS: AFs were isolated from thoracic aortas of 4-, 8-, 16-, and 24-week-old male SHR and Wistar-Kyoto (WKY) rats and cultured to passage 4. Proteomic differential expression profiles between SHR-AFs and WKY-AFs were investigated using 2-D electrophoresis (2-DE), whereas gel image analysis was processed using Image Master 2D Platinum. Protein spots were identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF-MS). Expression levels of annexin A1 in AFs and aortas from SHR and WKY rats were detected with Western blotting and immunofluorescence techniques. RESULTS: In 4-, 8-, 16-, and 24-week-old SHR-AFs, 49, 59, 54, and 69 protein spots were found to have significant differences from the age-matched WKY-AFs. Fourteen spots with the same changes in patterns were analyzed in 4-, 8-, 16-, and 24-week-old SHR-AFs with mass spectrometry. Except for cytoskeleton proteins such as tubulin beta 5, it was found that annexin A1, translation elongation factor Tu, endoplasmic reticulum protein 29 and calcium-binding protein 1 were expressed in vascular AFs and their levels changed significantly in SHR-AFs compared with those in WKY-AFs. A decrease in annexin A1 in SHR-AFs was confirmed with Western blotting and immunofluorescence staining at the cell and tissue levels. CONCLUSION: The application of proteomic techniques revealed a number of novel proteins involved in adventitial remodeling of AFs from SHR, which provide new mechanisms responsible for the occurrence and development of hypertension and potential targets for influencing vascular remodeling in hypertension.